2021
DOI: 10.1007/s10903-021-01273-w
|View full text |Cite
|
Sign up to set email alerts
|

Immigration Status as the Foundational Determinant of Health for People Without Status in Canada: A Scoping Review

Abstract: Migration is increasing at unprecedented rates worldwide, but inadequate mechanisms for granting citizenship or permanent residence have rendered many immigrants without legal status. We study the health of people without immigration status in Canada, building on a 2010 review on being without status and health. We employ an expanded definition of health, guided by the WHO Social Determinants of Health (SDoH) framework. Using a scoping review methodology, we reviewed literature from 2008 to 2018 on the SDoH of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Reasons for limited studies on medically uninsured populations include ethical barriers to study this population and limitations of existing data collection methods [ 52 , 53 ]. Gagnon et al (2021) who conducted a narrative scoping review on immigration status as a determinant of health, which we see as a complementary study to ours, showed that studies in this area are primarily qualitative in nature [ 16 ]. Our search also highlighted that literature is limited by the definition of medically uninsured.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Reasons for limited studies on medically uninsured populations include ethical barriers to study this population and limitations of existing data collection methods [ 52 , 53 ]. Gagnon et al (2021) who conducted a narrative scoping review on immigration status as a determinant of health, which we see as a complementary study to ours, showed that studies in this area are primarily qualitative in nature [ 16 ]. Our search also highlighted that literature is limited by the definition of medically uninsured.…”
Section: Discussionmentioning
confidence: 76%
“…Other exclusion criteria included notes, editorials, books, news reports, case reports, commentaries, opinions, and letters. Qualitative research was also excluded given that previous reviews have already summarized qualitative literature on this population in Canada [ 5 , 16 , 33 ]. In addition, we were interested in synthesizing the quantitative relationship between medical uninsurance and various outcomes (i.e., health outcomes, health care use, and cost) and understanding the size of the problems affecting the medically uninsured, for which quantitative research was relevant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reasons for limited studies on medically uninsured populations include ethical barriers to study this population and limitations of existing data collection methods (39,40). Gagnon et al (2021) who conducted a narrative scoping review on immigration status as a determinant of health, which we see as a complementary study to ours, showed that studies in this area are primarily qualitative in nature (41). Our search also highlighted that literature is limited by the de nition of medically uninsured.…”
Section: Discussionmentioning
confidence: 83%
“…With regards to FBT, many of the RCTs have been conducted with very specific populations—predominantly Caucasian/White, educated, and English‐speaking samples (Accurso et al, 2021; Agras et al, 2014; Le Grange et al, 2007; Lock et al, 2010, 2015)—putting into question their applicability for populations outside of these demographics. Given the high prevalence rates of EDs and disordered eating among adolescents in minoritized groups (particularly ethnic/racial minorities; Rodgers et al, 2018; Rodgers et al, 2017), and that migration rates continue to rise worldwide (e.g., Gagnon et al, 2022), adapting FBT to better suit diverse populations is of particular concern.…”
Section: Introductionmentioning
confidence: 99%